2020
DOI: 10.1590/1980-265x-tce-2019-0268
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nurses for Continuity of Care After Hospital Discharge

Abstract: Objective: to recognize the role of nurses to maintain continuity of care for users after hospital discharge. Method: an exploratory, descriptive study with a qualitative approach. The study was applied at hospital discharge originating from the most complex health center in Magallanes, the Hospital Clinico Magallanes, Chile. Data were collected through interviews with nurses, carried out between May and August 2018. To analyze the material, the content analysis technique was used. Results: three categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
2
3
0
3
Order By: Relevance
“…From the researcher point of view, this result may be due to nurses were interested were identified needs and requirements of elderly patients. This result is accordance with Guzmán, et al, (2020) (21) that conducted a study entitled "Role of nurses for continuity of care after hospital discharge" and found that majority of nurses had positive perception about total level of perception regarding discharge planning. Conversely, this result is in disagreement with Biese, et al, (2018) (22) that conducted a study entitled " Telephone follow-up for older adults discharged to home from the emergency department" and found that more than one third of nurses had negative perception about total level of perception regarding discharge planning.…”
Section: Discussionsupporting
confidence: 90%
“…From the researcher point of view, this result may be due to nurses were interested were identified needs and requirements of elderly patients. This result is accordance with Guzmán, et al, (2020) (21) that conducted a study entitled "Role of nurses for continuity of care after hospital discharge" and found that majority of nurses had positive perception about total level of perception regarding discharge planning. Conversely, this result is in disagreement with Biese, et al, (2018) (22) that conducted a study entitled " Telephone follow-up for older adults discharged to home from the emergency department" and found that more than one third of nurses had negative perception about total level of perception regarding discharge planning.…”
Section: Discussionsupporting
confidence: 90%
“…At the POP, nurses were the only HCW group that positively influenced a HP/DP variable. This findings corroborate the study of Guzmán, Ferreira, and de Andrade (2020) which highlighted the important role nurses played through care networks in ensuring continuity of nursing services for discharged patients [ 48 ].…”
Section: Discussionsupporting
confidence: 90%
“…Care coordination can be performed specifically among health professionals and both nurses and physicians have significant participation in the articulations between services (14) . In Chile, HC nurses concentrate their efforts to qualify the discharge process and team work, but, as in the present study, they do not have a formal monitoring system coordinated with the PHC, which may imply risks for the patient (25) with potential impacts on the clinical outcome (26) .…”
Section: Discussionmentioning
confidence: 89%
“…Another challenge reported by the HC nurses is the agility of the PHC response (before 72 hours), thus meeting the patient's conditions for discharge, the demands for hospitalization (bed occupancy) and the de-hospitalization process anticipated in the responsible discharge movement (7) . In this regard, RAS services shall establish an active channel of communication and follow-up at discharge, ensuring feedback and planning for the continuity of care (25) .…”
Section: Discussionmentioning
confidence: 99%